Novel resonant multi-soliton solutions of time fractional coupled nonlinear Schrödinger equation in optical fiber via an analytical method - Jamshad Ahmad; Sobia Rani; Nasser Bin Turki; Nehad Ali Shah (Results in Physics, 2023)
The aim of this article is to investigate the time fractional coupled nonlinear Schrödinger equation (TFCNLSE) which can be used to describe the interaction among the modes in nonlinear optics and Bose–Einstein condensation. The TFCNLS equation plays a crucial role in soliton wavelength division multiplexing and pulse propagation through a two-mode optical fiber. For the sake of getting different analytical solutions, we capitalize modified version of the extended tanh-expansion method. Fractional nonlinear partial differential equations (FNLPDEs) have become popular because they can explain complex physical phenomena and have dynamic structures of localized wave solutions. The study obtained various soliton solutions including bright, dark, periodic, and singular solitons. The results are presented in graphical form with appropriate parameter values to aid visualization. Such solutions are critical for explaining some mesmerizing and complex physical phenomena. In addition, some results from earlier studies are generalized which justify the novelty of the current study. This study proves that the computational method used is efficient, brief, and widely applicable in finding analytical solutions to diverse complex nonlinear problems arising in the recent era of nonlinear optics, applied sciences and engineering.